2017
DOI: 10.1016/j.gheart.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Interethnic Differences in Serum Lipids and Implications for Cardiometabolic Disease Risk in African Ancestry Populations

Abstract: African Americans are generally found to have a healthier lipid profile (lower triglycerides [TG] and higher high-density lipoprotein cholesterol concentration [HDLC]) compared to those of other ethnicities. Paradoxically, African Americans do not experience a decreased risk of the cardiometabolic diseases that serum lipids are expected to predict. This review explores this mismatch between biomarker and disease among African ancestry individuals by investigating the presence of interethnic differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 113 publications
(148 reference statements)
3
48
0
Order By: Relevance
“…Lower visceral fat deposition has been extensively reported in black populations compared with other ethnic groups [ 5 ] and we hypothesised that, consequently, BAM would exhibit greater adipose tissue and hepatic insulin sensitivity. Although our data did not show a significant relationship between adipose insulin sensitivity and VAT, which may be due to the sample size, we did detect lower VAT and a possible, but non-significant, trend towards lower basal lipolysis in our BAM group, which agrees with the majority of the literature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lower visceral fat deposition has been extensively reported in black populations compared with other ethnic groups [ 5 ] and we hypothesised that, consequently, BAM would exhibit greater adipose tissue and hepatic insulin sensitivity. Although our data did not show a significant relationship between adipose insulin sensitivity and VAT, which may be due to the sample size, we did detect lower VAT and a possible, but non-significant, trend towards lower basal lipolysis in our BAM group, which agrees with the majority of the literature.…”
Section: Discussionmentioning
confidence: 98%
“…The pathophysiological processes of type 2 diabetes are well documented and include beta cell dysfunction, ectopic fat deposition and insulin resistance of the liver, skeletal muscle and adipose tissue [ 2 , 3 ]; the use of stable isotopes has enabled measurement of these tissue-specific sites of insulin resistance [ 4 ]. Black populations typically display lower visceral adipose tissue (VAT) and hepatic fat deposition and a more favourable blood lipid profile [ 5 ]. Visceral fat has been positively associated with hepatic and adipose tissue insulin resistance in diabetes and normal glucose tolerance [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that whites have higher levels of very low density lipoprotein cholesterol (VLDL-C) and TG, as well as, slightly lower HDL-C levels compared with blacks [12]. The differences in factors like body fat distribution, activity of enzymes involved in lipid hydrolysis, insulin response, and some specific apolipoproteins can partly explain the interethnic differences in serum lipids [13]. Many countries use the NCEP pediatric cutpoints for screening the lipid disorders without consideration of possible ethnic differences.…”
Section: Introductionmentioning
confidence: 99%
“…The associations of genetic ancestry with complex disease are varied, with some data suggesting that greater African ancestry is protective, whereas other data suggest the opposite. [19][20][21] It is known that APOL1 high-risk genotype frequencies vary within African descent populations, and adjustment for population substructure revealed confounding for the relationship between APOL1 and survival in our data. Given heterogeneity in African descent populations in the United States and the decrease in our sample size on adjustment for ancestry, larger studies are needed to investigate this relationship.…”
Section: Discussionmentioning
confidence: 50%